AB1131 HIGH-RESOLUTION ULTRASOUND ASSESSMENT OF CARTILAGE THINNING IN RHEUMATOID ARTHRITIS. (June 2019) - Cipolletta, Edoardo; Filippucci, Emilio; Matteo, Andrea DI; Carlo, Marco DI; Salaffi, Fausto; Grassi, Walter
Abstract : Background: Conventional radiography is the standard imaging modality to detect joint damage in rheumatoid arthritis (RA). Ultrasound (US) allows for a direct visualization of hyaline cartilage. To date, only few studies investigated the role of US in the assessment of cartilage damage in RA. Objectives: To compare US qualitative and quantitative assessments of cartilage thinning at metacarpal head (MH) in RA patients and in an age-, sex- and height-matched healthy controls (H). To correlate cartilage damage and clinical parameters in RA. Methods: US examination was performed on 318 metacarpophalangeal (MCP) joints of 40 consecutive RA patients and on 320 MCP joints of 40 age-, height- and sex-matched H using a MyLab Twice (Esaote Biomedica, Genoa, Italy), equipped with a high frequency linear probe (up to 22 MHz). RA patients were enrolled according to the 2010 RA classification criteria. The hyaline cartilage of MH from II to V digits of both hands was examined with the MCP joints in maximal flexion. Each MH was scanned in longitudinal and transverse views. Particular attention was paid on maintaining the probe in a position providing an angle of 90° between the direction of the US beam and the cartilage surface 1 . Cartilage thickness (CT) was assessed both semi-quantitatively (using a reliable qualitative five-grade scoring system 2 ) and quantitatively (using the mean value of longitudinal and transverse measurements of the CT). Finally, association between cartilage damage and clinical parameters was assessed. Results: Semiquantitative score: Cartilage thinning (grade 2, 3 and 4) was found in at least one MH in 23 RA patients (57.5%) and in 4 H (10.0%) (p<0.01). A significantly higher prevalence of cartilage damage (grade 2, 3 and 4) at joint level was found in RA patients (86 MCP joints, 27.0%) in comparison with H (13 MCP joints, 4.1%) (p<0.01). Quantitative assessment: CT of the MH ranged from 0.0 to 1.10 mm (0.60±0.26 mm, mean±SD) in RA patients and from 0.41 to 1.08 mm (0.67±0.12 mm, mean±SD) in H. Male had a thicker hyaline cartilage than female, both in RA patients (p<0.01) and in H (p<0.01). No significant difference was found between left and right side, both for RA patients (p=0.48) and healthy subjects (p=0.94). Detailed quantitative measurements of CT of MH are reported in table 2 . 95%CI: 95% confidence interval; L : left; MH : metacarpal head; R : right; RA : rheumatoid arthritis; SD : standard deviation; US : ultrasound. A significant association was found between the CT value and age (r=-0.528, p<0.001), disease duration (r=-0.376, p=0.005) and grade of the semiquantitative scoring system (r=-0.80, p<0.001). No association was found between CT and BMI, weight, ACPA positivity and RF positivity. Conclusion: This study demonstrated that a significantly higher prevalence of cartilage damage was found in RA patients using both the semiquantitative score and the quantitative assessment. In particular, in RA patients the hyaline cartilage of II and III MH is thinner in comparison with H. Finally, a significant association was found between the CT values and disease duration and age. References: [1] Torp-Pedersen S, Bartels EM, Wilhjelm J, Bliddal H. Articular cartilage thickness measured with US is not as easy as it appears: a systematic review of measurement techniques and image interpretation. Ultraschall Med. 2011;32:54-61. [2] Filippucci E, da Luz KR, Di Geso L, et al. Interobserver reliability of ultrasonography in the assessment of cartilage damage in rheumatoid arthritis. Ann Rheum Dis. 2010;69:1845-8. Disclosure of Interests: Edoardo Cipolletta: None declared, Emilio Filippucci: None declared, Andrea Di Matteo: None declared, Marco Di Carlo: None declared, Fausto Salaffi Grant/research support from: Abbvie, Roche, Novartis, BMS, Pfizer, Sanofi, Speakers bureau: Abbvie, Roche, Novartis, Pfizer, Sanofi, BMS, Walter Grassi: None declared